The study of the effects of different surfactants, concentration of PVA and molecular weight of PLGA on the development of Gentamicin-loaded PLGA microspheres - Harun Ismail, Ahmad Fahmi; Doolane, Abd Monem; Mohamed, Farahidah (unknown, 2010)
Mycoplasma pulmonis is one of the major causes for arthritis which can be treated with Gentamicin. The fabrication of Gentamicin with PLGA micropsheres by using multiple-emulsion (w/o/w) solvent evaporation method can be used to treat this disorder. The resultant micropsheres were characterized with scanning electron microscopy (SEM) for external morphology and the size analysis was done by using laser diffraction. The encapsulation efficiency was carried out using ninhydrin assay method to quantify the Gentamicin concentration by UV spectrophotometer at 400 nm. Our aim was to investigate the effects of using different concentration of PVA, different molecular weight of PLGA and different types of surfactants on several parameters which included external morphology of the micropsheres, the size distribution, the encapsulation efficiency and also in-vitro release profile of Gentamicin. Our result showed that the concentration of PVA was inversely proportional to the size of micropsheres as 1% PVA yielded mean size distribution of micropsheres around 13.68 μm (± 0.052 μm) whereas 5% of PVA yielded 3.78 μm (± 0.008 μm). This ongoing research is aimed to transfect Gentamicin-loaded PLGA micropsheres onto Human Osteosarcoma Cell Line (Saos-2). Success of the study will indicate promising use of a novel Gentamicin delivery system for therapy in bone diseases.